2014
DOI: 10.1080/01448765.2014.964317
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming biotic and abiotic stresses in the Solanaceae through grafting: current status and future perspectives

Abstract: This paper reviews the status of the use of grafting in two solanaceous crops of global importance, tomato and eggplant, for the control of biotic and abiotic stresses. Flooding and soil-borne diseases cause severe crop losses of tomato during the hot and wet summer months in the lowland tropics. Asian Vegetable Research and Development Center (AVRDC) recommended since 2003 the use of eggplant rootstocks VI046103 (EG195) and VI045276 (EG203) for grafting tomato scions to provide a high degree of tolerance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 48 publications
0
40
0
3
Order By: Relevance
“…This requires identifying a suitable combination of scion and rootstock with higher yield and resistances to abiotic and biotic stress while preserving the quality requirements of the fruit or vegetable. Although grafting is widely used in Asia, it is not widespread in Africa (Keatinge et al 2014). To introduce grafting systems in Africa, a vibrant and effective seedling system is needed, which is currently only the case in Ethiopia.…”
Section: Changes In Cropping Systems Induced By Protected Cultivationmentioning
confidence: 99%
“…This requires identifying a suitable combination of scion and rootstock with higher yield and resistances to abiotic and biotic stress while preserving the quality requirements of the fruit or vegetable. Although grafting is widely used in Asia, it is not widespread in Africa (Keatinge et al 2014). To introduce grafting systems in Africa, a vibrant and effective seedling system is needed, which is currently only the case in Ethiopia.…”
Section: Changes In Cropping Systems Induced By Protected Cultivationmentioning
confidence: 99%
“…For example, Sanogo et al [51] observed a 140% increase in vascular wilt severity caused by Verticillium dahliae in waterlogged chili pepper (Capsicum annuum L.) plants compared to non-waterlogged plants. Flooding and soil-borne diseases can cause severe crop losses of tomato during the hot and wet summer months in the tropics [52]. Villarreal-Navarrete et al [6] also observed a greater progress of vascular wilt caused by FO in cape gooseberry under waterlogging conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Although vegetable grafting has been known for a long time, it is being used increasingly worldwide on Solanaceae and cucurbit crops (Kubota et al, 2008;Lee et al, 2010). The merits of vegetable grafting for increasing resistance to abiotic and biotic stress have been discussed in several recent reviews, which stressed its potential for tackling food security issues (Keatinge et al, 2014;Rouphael et al, 2018). The broad genetic diversity of the Solanaceae family has encouraged researchers to improve the performance of tomato plants (S. lycopersicum) by using different rootstocks from the same species (homografting), but also from different species (heterografting), such as eggplant (S. melongena), african eggplant (S. macrocarpon and S. aethiopicum), and wild species (S. torvum and S. integrifolium) (Lee and Oda, 2003).…”
mentioning
confidence: 99%